Gugatan Lain-Lain Oleh Kreditor Kepada Debitor Pasca Berakhirnya Kepailitan - Maulana Farras; Elfrida R Gultom (Fakultas Hukum Universitas Islam Malang, 2023)
The purpose of this study is to discuss legal remedies for other lawsuits filed by creditors after the end of bankruptcy where creditors still have unpaid receivables and debtors themselves make additional capital after the bankruptcy is declared over. This study uses a normative juridical research method with a statutory and case approach. Based on this case, other lawsuits filed by creditors were granted by the commercial court judge and finally the bankruptcy process was reopened. There are legal remedies for other lawsuits that have been appropriately filed by creditors to debtors who have not paid off their debts, then make additional capital even though the bankruptcy process has been declared.